2017
DOI: 10.2147/ott.s140062
|View full text |Cite
|
Sign up to set email alerts
|

Serum exosomal miR-125b is a novel prognostic marker for hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the sixth most common cancer worldwide with high mortality. Circulating miRNA has been demonstrated as a novel noninvasive biomarker for many tumors. This study aimed to investigate the potential of circulating miR-125b as a prognostic marker of HCC. Exosomes were extracted from serum samples collected from two independent cohorts: cohort 1: HCC (n=30), chronic hepatitis B (CHB, n=30), liver cirrhosis (LC, n=30); cohort 2: HCC (n=128). We found that miR-125b levels were remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 32 publications
5
92
0
1
Order By: Relevance
“…This finding is consistent with that of previous studies focusing on other cancers [7][8][9][10][11]. Another study also found that a high expression of miR-125b and some other adverse factors (i.e., FLT3 mutation and MLL mutation) had a synergistic effect, and showed a 4-to 8-fold increased risk of relapse and overall death in patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is consistent with that of previous studies focusing on other cancers [7][8][9][10][11]. Another study also found that a high expression of miR-125b and some other adverse factors (i.e., FLT3 mutation and MLL mutation) had a synergistic effect, and showed a 4-to 8-fold increased risk of relapse and overall death in patients.…”
Section: Discussionsupporting
confidence: 91%
“…MiR-125b may predict prognosis in several types of digestive, respiratory, and nervous system cancers partly through regulating cell migration, invasion, and therapeutic response [7][8][9][10][11][12][13][14]. The potential role of miR-125b in hematological malignances has also been explored in cell, animal, and tissue levels [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism by which miR-125b regulates MM remains unknown. Importantly, circulating miR-125b-5p has been reported to be correlated with colorectal cancer (30), breast cancer (31) and hepatocellular carcinoma (32). Circulating and serum-derived miRNAs have also been identified in MM patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…High expression of HOXB8 plays an important role in the progression and recurrence of HCC [20] . Exosomes extracted from serum samples collected from two cohorts of HCC patients showed high levels of miR-125b which was an independent predictive factor for postoperative recurrence and overall survival of HCC patients [39] . Serum exosomal miR-665 levels were significantly higher in HCC patients than those in healthy subjects.…”
Section: Exosomal Rna Biomarkersmentioning
confidence: 92%